Effect of titanium dioxide (TiO2) distribution and minute amounts of carbon black on the opacity of PVDF based white composite films. Issue 9 (5th November 2015) - Li, Tongbing; Sheng, Dekun; Xiong, Zhengrong; Gao, Xiumei; Ji, Fance; Yang, Yuming
ABSTRACT: There is a contradiction in making completely opaque and white plastic film with a required high TiO2 filling fraction, which resulted in inefficient pigment utilization and high cost. Two methods were used here to overcome the contradiction. Firstly, TiO2 was grafted with poly(methyl methacrylate) (PMMA) by atom transfer radical polymerization to improve the pigment dispersion in poly(vinylidene) fluoride (PVDF). Secondly, minute amounts of carbon black (CB) were added into the PMMA‐ g ‐TiO2 /PVDF system to enhance opacity and decrease TiO2 fraction. The structure, morphology, and properties of PMMA‐ g ‐TiO2 hybrid particles and composite films were investigated by FTIR, TEM, TGA, SEM, DMA, covering power meter, and UV/VIS spectrophotometer, etc. It was observed that PMMA‐ g ‐TiO2 was dispersed uniformly as individual particles in PVDF due to the good compatibility between PMMA and PVDF. Therefore, the opacity of PMMA‐ g ‐TiO2 /PVDF films was markedly higher than unmodified‐TiO2 /PVDF ones. Adding minute amounts of CB can significantly increase the opacity of the thin film due to its absorption effect on decreasing light transmittance. The contrast ratio (CR) of the PMMA‐ g ‐TiO2 /PVDF film with 20 μm thickness and 25 vol % TiO2 was 97.67%, lower than the critical CR 98% for a complete opacity, however, the CR of sample with 10 vol % TiO2 was 98.1% as the CB concentration was 2 × 10 −4 g/cm 3, saved more than 15% TiO2 . We proposed that a critical thickness d 0 existed for the CB/PMMA‐ g ‐TiO2 /PVDF composite films, under which the light reflectance increased as a function of thickness, otherwise, the reflectance kept constant. Besides, d 0 could be decreased by increasing CB concentration. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43064. Abstract :